Application research on low cost support method for surrounding rock of broken section roadway in phosphate mine area - Xu, Mengchao; Li, Xiaoshuang; Wang, Jiawen; Cao, Mengzhen; Wang, Menglai; Li, Shujian (Frontiers in Earth Science, 2024)
Introduction: Taking a phosphate mine in Yunnan as the engineering research background, the fractured rock mass of the No. 1 belt roadway is selected as the research object. Methods: To reduce the cost of tunnel surrounding rock support and optimize construction technology, a combination of numerical simulation software Midas and on-site experiments was used to compare and analyze the distribution characteristics of the plastic zone of tunnel surrounding rock, deformation characteristics of tunnel surrounding rock, and stress characteristics of tunnel support anchor bolts under two support methods: double-layer spray anchor mesh and single-layer spray anchor mesh with steel bar. Results: Research findings indicate that adopting the single-layer spray anchor mesh with steel bar support method results in a more uniform distribution of the plastic zone at the top of the tunnel surrounding rock, with a smaller range. The settlement of the roof and bulging of the bottom plate in the roadway’s surrounding rock, supported by a single-layer spray anchor mesh and steel bars, measure at 75.033 mm and 82.165 mm, respectively. Additionally, the internal bulging on both sides of the roadway’s surrounding rock is recorded as 37.835 mm and 37.470 mm, respectively. On the other hand, when utilizing a double-layer spray anchor mesh for support, the settlement of the roof and bulging of the bottom plate in the roadway’s surrounding rock are measured at 84.199 mm and 85.255 mm, respectively. Correspondingly, the internal bulging on both sides of the roadway’s surrounding rock records measurements of 41.670 mm and 41.756 mm, respectively. Furthermore, adopting the single-layer spray anchor mesh with steel bar support method ensures a more even transfer of axial forces to the steel bars, thereby increasing the overall load-bearing capacity. In contrast, the anchor bolts in the double-layer spray anchor mesh support method experience higher axial forces, leading to more pronounced stress concentration. Discussion: By comparing the field monitoring data, it is evident that the single-layer spray anchor mesh with steel bar support method exhibits significantly better control over the tunnel surrounding rock than the double-layer spray anchor mesh support method. Therefore, replacing the double-layer spray anchor net support with a single-layer spray anchor net with steel bar support method is entirely feasible and can meet on-site practical production requirements. The research results hold significant value in providing guidance and reference for selecting cost-effective support schemes for tunnel surrounding rock.